Edukasi tentang Pengaruh Kebiasaan Mengkonsumsi Makanan dan Minuman Manis secara Berlebih bagi Kesehatan - Ira Marti Ayu; Namira W Sangadji; Andi Shalsabila Putri; Azzahra Putri Indarg; Shafira Azuraa; Marito Elisha Hofman Panjaitan; Adinda Putri Syahrani; Anfrew Leoranz Purba; Fitrotul Hasanah; M Rafi Favianto (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
Preliminary study showed that many people consume sugary foods and beverages daily. This behavior has also become a habit for the people in Rukun Tetangga 02, both adults and children. It can lead to non-communicable diseases. This activity was carried out to increase community’s knowledge regarding the habit of consuming sweet foods and drinks. To know whether the counseling is effective or not, we gave Pre-test and Post-test to measure changes in the community’s level of knowledge. This activity was attended by 15 residents aged> 20 years. The results of this activity show that there is an increase in knowledge. There were 93.3% answered correctly about the information on sugar content in packaging, 96.7% answered correctly about sugar consumption limits, and 86.7% answered that foods naturally contain sugar and the impact of consuming excess sweet food. In addition, around 80.0% answered correctly about how to reduce the consumption of sweet food. This activity also found that as many as 60% and 66.6% of participants consumed sweet foods and drinks in cakes and tea, and 33.3% consumed 2 to 4 times daily. In addition, as much as 33.3% use 3 measuring spoons of sugar in a day